Sur les réseaux de plusieurs dimensions dans l’espace euclidien - Basilev, V. (Lithuanian Mathematical Journal, 1966)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: В. Т. Базылев. О многомерных сетях в евклидовом пространстве V. Bazylevas. Daugiamačių tinklų euklidinėje erdvėje klausimu